Factors affecting Customer Satisfaction in regard of Life Insurance (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
In life, uncertainty is a fundamental element. This ambiguity causes us to fear taking chances in our lives. By taking all possible effort to prevent risk, one can allay their fear of it. Even with every care, accidents happen. Therefore, insurance is among the finest ways to deal with this uncertainty. It is critical to recognize that danger is an inherent aspect of every individual's life. Life insurance, then, is an instrument that provides benefits to protect a person's life. Today Life insurance has grown as a very major sector serving innumerable clients and this fact is very well known that no industry can survive without satisfying its customers and insurance industry is no different. The purpose of this study is to look into the elements that influence customer satisfaction in the life insurance sector. According to the study's findings, a number of aspects affect customer satisfaction, such as the level of customer service, the company's transparency and reliability, the range and the suitability of the insurance plans provided, as well as the effectiveness and simplicity of the claims procedure.